2020
DOI: 10.20944/preprints202005.0493.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diabetic Retinopathy Diagnostics from Retinal Images based on Deep Convolutional Networks

Abstract: Retinopathy is a human eye disease that causes changes in retinal blood vessels that leads to bleed, leak fluid and vision impairment. Symptoms of retinopathy are blurred vision, changes in color perception, red spots, and eye pain. In this paper, a new methodology based on Convolutional Neural Networks (CNN) is developed and proposed to diagnose and give a decision about the presence of retinopathy. The CNN model is trained by different images of eyes that have retinopathy and those which do not have retinopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
(40 reference statements)
0
4
0
2
Order By: Relevance
“…It leads to offer tools for automated learning from the history of data and developing models to discover the outcomes of future scenarios. There are the various tools for data mining machine learning algorithms to identify and predict the various disease in terms of regression, decision tree and Bayesian network [17]. Finding of a disease, needed different test results in variety of scenarios with respect to the particular patient.…”
Section: Literature Surveymentioning
confidence: 99%
“…It leads to offer tools for automated learning from the history of data and developing models to discover the outcomes of future scenarios. There are the various tools for data mining machine learning algorithms to identify and predict the various disease in terms of regression, decision tree and Bayesian network [17]. Finding of a disease, needed different test results in variety of scenarios with respect to the particular patient.…”
Section: Literature Surveymentioning
confidence: 99%
“…Based on this discussion, it can be concluded that it is difficult to manually detect retinal eye diseases from OCT images, as it is a complicated and laborious task that can now be automated through the use of deep learning. Although various deep learning-based automated methods have been presented in the literature, the majority of them employ only deep CNN models and do not incorporate any feature selection techniques [ 40 ]. The proposed selection-based approach, which employs the modified ResNet-50, InceptionV3, and DenseNet-201 models, provides a reliable method for early and precise detection of various retinal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Penambangan data adalah teknik mengekstraksi data dari basis data besar menggunakan algoritme khusus untuk mengidentifikasi pola dan tren yang berguna. [4] Penambangan data adalah teknik analisis data yang secara otomatis dan cepat mengeksplorasi dan menemukan pola dan informasi tersembunyi dalam data [5] neural network adalah Neural network adalah suatu model matematis yang terinspirasi dari struktur dan fungsi otak manusia, dan digunakan untuk mempelajari pola-pola kompleks dalam data [6] Pada penelitian serupa [7] membahas tentang penerapan data mining dengan dengan Neural Network Backprogation dapat digunakan untuk untuk memprediksi harga saham pada tiga golongan bedasarkan kapitalisasinya. Pada penelitian [8] penerapan data mining dengan menggunakan Artificial Neural Network digunakan untuk untuk memprediksi harga saham BCA Tbk.…”
Section: Pendahuluanunclassified